Trellis‐coded CIOD using conjugate symmetric rotated QAM signal set. Issue 13 (1st June 2013) - Kim, C.J.; Heo, S.W.; Lee, H.K.
Abstract : A trellis‐coded coordinate‐interleaved orthogonal design (TC‐CIOD) for four transmit antennas with a rotated QAM base signal set is introduced. To design a high rate pre‐encoder the base signal set is expanded by conjugating the rotated QAM signals without changing the transmit signal set at each transmit antenna. The proposed TC‐CIOD provides coding gain without increasing peak‐to‐average‐power ratio.